Advances in Use of Keratinase from Feather Wastes for Feedstock Modification - Koentjoro, Maharani Pertiwi; Nugroho Prasetyo, Endry (Applied Food Biotechnology, 2020)
Background and Objective: Enzymatic modification of protein-base materials is fast emerging as a promising tool for chemical catalysts based on increasing knowledge in enzyme reaction and devotion to achieve sustainable systems. Enzymes actively used in protein modification include proteases, especially keratinases, and their most interesting features include ability to degrade keratin to finer molecules. This review summarizes strategies for the modification of keratin using keratinase to increase functional protein-based feedstocks up-to-date. Results and Conclusion: Keratinases are useful safe agents for feather waste modification in animal feeds. Modification can be carried out either using whole microbial cells or enzyme activities through fermentation processes in costeffective environmental-friendly manners. In this study, promising outcomes in feather waste management were achieved and hence studies can be continued to treat wastes of other sources. Conflict of interest: The authors declare no conflict of interest.